2018
DOI: 10.1016/j.kint.2017.08.011
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial indicates that levamisole increases the time to relapse in children with steroid-sensitive idiopathic nephrotic syndrome

Abstract: Levamisole has been considered the least toxic and least expensive steroid-sparing drug for preventing relapses of steroid-sensitive idiopathic nephrotic syndrome (SSINS). However, evidence for this is limited as previous randomized clinical trials were found to have methodological limitations. Therefore, we conducted an international multicenter, placebo-controlled, double-blind, randomized clinical trial to reassess its usefulness in prevention of relapses in children with SSINS. The efficacy and safety of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 22 publications
2
67
0
Order By: Relevance
“…16,17 These results were confirmed in a recently published, placebo-controlled, multicenter randomized controlled trial that showed that levamisole prolonged the time to first relapse by 78% and resulted in a higher proportion of patients in sustained remission at 1 year (26% vs. 6%). 1 The present study, designed to withdraw steroids by 4 months, also showed that more than one-third of patients treated with levamisole were in sustained remission at the 1-year follow-up evaluation. Although subgroup analysis in the former study showed a possible difference in disease response to levamisole between patients from Europe and India, confounding by disease severity cannot be ruled out.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…16,17 These results were confirmed in a recently published, placebo-controlled, multicenter randomized controlled trial that showed that levamisole prolonged the time to first relapse by 78% and resulted in a higher proportion of patients in sustained remission at 1 year (26% vs. 6%). 1 The present study, designed to withdraw steroids by 4 months, also showed that more than one-third of patients treated with levamisole were in sustained remission at the 1-year follow-up evaluation. Although subgroup analysis in the former study showed a possible difference in disease response to levamisole between patients from Europe and India, confounding by disease severity cannot be ruled out.…”
Section: Discussionsupporting
confidence: 68%
“…Levamisole was effective chiefly in patients with frequent relapses, the predominant disease subtype among Indian patients; those with steroid dependence, usually of European ancestry, did not respond as well. 1 Similarly, exploratory post hoc analysis in the present study suggests that the time to first relapse was similar for levamisole and MMF among frequent relapsers, but longer for MMF than levamisole in steroid dependence. The frequency of relapses, our chief outcome, has been reported previously in 2 trials.…”
Section: Discussionsupporting
confidence: 62%
“…After more than 3 decades, its use has been accurately investigated in a recent randomized controlled trial in which its efficacy was compared with placebo in 99 children with frequently relapsing nephrotic syndrome from 6 countries; the children were treated for 12 months. 7 This study showed that levamisole prolonged the time to relapse by 78%, with 26% of patients in remission at 12 months of treatment versus 6% in the placebo group. A subgroup analysis suggested ethnic differences in response to treatment, with a higher effectiveness of levamisole in the group of children from India, but in fact these children mainly had frequently relapsing nephrotic syndrome (68%), whereas the children of European ancestry mainly had steroid-dependent nephrotic syndrome (89%).…”
mentioning
confidence: 80%
“…1 It continues to be used in certain countries for its therapeutic benefit in childhood nephrotic syndrome. 2 Despite Food and Drug Administration regulation, levamisole has continuously been used as a cocaine adulterant due to its synergistic effect with cocaine, leading to an increase in dopamine transmission, and its physical similarity to cocaine, making the sample appear purer. 3,4 CLIVS is identified by its cutaneous manifestations, neutropenia, and ANCA positivity.…”
Section: Discussionmentioning
confidence: 99%